Lungs’ Microscopic Patterns of Vessels in Patients Deceased with or by SARS-CoV-2 Infection (Medico Legal Update, 2021)
Background: Even If Specific mechanisms are not completely understood, several studies highlightedSevere Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) ability to alter vascular homeostasis.In the literature, multiple reports of microscopic pulmonary findings of vascular structures in patientsdeceased by or with SARS-Cov-2 infection are available. Nevertheless, the scientific literature lacks asystematic analysis of these findings. Methods: the authors realized a systematic review of the literature inorder to identify common microscopic patterns representative of pulmonary vascular damage: useful datafor pathologists in clinical and forensic settings. The research yielded 23 articles (79 total cases). Quali/quantitative analysis was carried out. Conclusion: the review allowed to identify vascular thrombosis(especially in lesser caliber vessels) as common microscopic pattern. The recurrence of this pattern wasconfirmed by scientific literature data which demonstrate SARS-CoV-2 ability to interfere with coagulationcascade. Other meaningful microscopic findings were also discussed, even if their low frequency in studypopulation did not allow to define them as common